Mutual Fund Flows and the Supply of Capital in Municipal Financing - Adelino, Manuel; Cheong, Sophia Chiyoung; Choi, Jaewon; Oh, Ji Yeol Jimmy (Review of Financial Studies, 2026)
This paper investigates how capital supply from mutual funds affects municipal bond financing, making three key contributions. First, we introduce an identification strategy using the rule-based update of Morningstar ratings for 5-year-old funds, isolating supply-side effects from fund and issuer fundamentals. The results indicate that exogenous fund flows increase bond issuance probability and decrease yields. Second, these fund flows lead to more issuances when funds and issuers are connected through underwriters, highlighting relationship lending in municipal bond financing. Third, municipal issuers leverage favorable financing conditions for new issuance of revenue bonds, which translates into higher local house prices.